A STUDY ON MEDICINAL PLANTS USED IN KARKIDAKA KANJI: A HEALTH TRADITION OF KERALA - Mohan Deepa; Sajeevan Aiswaraya (International Journal of Ayurveda and Pharma Research, 2021)
Karkidakam (July- August) is the last month of Malayalam calendar and is one of the months that falls under monsoon season. The month is regarded as the most suitable time for rejuvenation therapies. Karkidaka chikitsa are well known tradition of Kerala, which focuses on detoxification of the body and prevention of monsoon related diseases. Karkidaka kanji is a medicated porridge consumed by the people as the part of Karkidaka chikitsa. The kanji increases the digestive capacity and strengthens the body. It is believed that the kanji will be providing immunity for the upcoming year. The present work reveals the importance of Karkidaka kanji and the plants used in the conventional method of its preparation. The information regarding the plants used was obtained from the Ayurvedic Doctors, Ayurvedic practitioners and local peoples of different regions of Kerala. The study enumerates the list of 87 plant species belonging to 42 families to be used in the preparation of Karkidaka kanji. The kanji is generally prepared using Njavara rice, spices and various other herbs like Sida cordifolia, Boerhavia diffusa, Mimosa pudica, the extract of ‘Dashapusham’ etc. The ingredients and preparation of Karkidaka kanji varied in different region according to the availability of plants. These ingredients are therapeutically active source of drug for various disease and ailments. Still there exists a lot of possibilities for investigating the potential pharmacological activates of these plants. Thus systematic documentation of such traditional system indicating the importance of plants opens up the opportunity for future research.